(untitled) (Hilo Analítico, 2025)
Music, as an artistic phenomenon inherent to human life, does not correspond to an exclusive means of entertainment throughout history; instead, it has been a reflection of the social, political, and cultural dynamics of each era. Thus, music consolidates itself as a tool for the transmission, expression, representation, and diversification of social fabric. In this way, an approach to understanding music as a mobilizer and indicator of social change is presented, based on reflections that, from various authors and perspectives, it is possible to develop, with the aim of broadening the perception of its impact and transformative potential in society, as well as the possible implications it may involve in everyday life.